Anti-inflammatory activity of 2-(5-((theophylline-7'-yl)methyl)-4-R-4H-1,2,4-triazole-3-ylthio)acetic acid salts - A. S. Gotsulya (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2014)
Inflammatory process is the leading pathogenic link of many diseases, which constitute about 80% of all pathologies in medical practice of any physician profession. Currently in a complex therapy of acute and chronic diseases a large number of drugs mainly from the group of non-steroidal anti-inflammatory drugs (NSAIDs) and glucocorticosteroids areusedas analgesics and anti-inflammatory preparations.